2014
DOI: 10.1074/jbc.m113.536748
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Phosphoenolpyruvate Carboxykinase Is Regulated by Redox Mechanisms and Interaction with Thioredoxin

Abstract: Background: Phosphoenolpyruvate carboxykinase (Pck) catalyzes the interconversion of phosphoenolpyruvate and oxaloacetate but typically prefers gluconeogenic formation of phosphoenolpyruvate. Results: Interactions of Mycobacterium tuberculosis (MTb) Pck with thioredoxin and reducing environments favor the anaplerotic oxaloacetate synthesis. Conclusion: A mechanism explaining the regulation of Pck functions is proposed. Significance: Regulation of Pck is important for the MTb non-replicative state associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 34 publications
0
45
0
Order By: Relevance
“…Mtb Pck is a GTP-dependent enzyme that under standard conditions catalyzes the gluconeogenic reaction leading to production of PEP. However, under reducing conditions, it favors the anaplerotic OAA synthesis [ 16 ]. The role of Pck in fixation of CO 2 during OAA biosynthesis has also been reported for slowly or intracellularly growing Mtb [ 17 , 18 ] and Mtb cultivated in conditions mimicking hypoxia arrest [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mtb Pck is a GTP-dependent enzyme that under standard conditions catalyzes the gluconeogenic reaction leading to production of PEP. However, under reducing conditions, it favors the anaplerotic OAA synthesis [ 16 ]. The role of Pck in fixation of CO 2 during OAA biosynthesis has also been reported for slowly or intracellularly growing Mtb [ 17 , 18 ] and Mtb cultivated in conditions mimicking hypoxia arrest [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The gene expression of Trx is also increased under hypoxic conditions. These findings suggest the presence of a regulatory mechanism by which M. tuberculosis responds to hypoxia and then adjusts metabolic activity to adapt to low-oxygen environments [12].…”
Section: Dissecting M Tuberculosis Pathogenesis From Protein Interacmentioning
confidence: 98%
“…The gene expression of Trx is also increased under hypoxic conditions. These findings suggest the presence of a regulatory mechanism by which M. tuberculosis responds to hypoxia and then adjusts metabolic activity to adapt to low-oxygen environments [12].As an intracellular pathogen, M. tuberculosis encounters oxidative stress throughout its life inside the host environment. Trx is the major protein disulfide reductase responsible for maintaining the redox state of the cytosol.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, like the case for ICL, these studies identified pckA as a clear determinant of persistence but failed to reveal its specific metabolic role, owing to limitations in the accuracy and completeness of bio-informatic annotations and in vitro biochemical studies. Indeed, follow on biochemical studies demonstrated that M. tuberculosis ’s PckA could catalyze the reverse reaction in an anaplerotic, rather than gluconeogenic, direction under reducing conditions such as those associated with hypoxia (103). Experimentally-based computational models of metabolic flux have similarly suggested that M. tuberculosis PckA may operate in an anaplerotic direction during intracellular growth within a THP-1 macrophage-like cell line (55).…”
Section: Measurementsmentioning
confidence: 99%